Assessing the global flux of organic carbon transported from terrestrial surfaces to oceans by rivers - Fei Chen; Xiaoyong Bai; Guangjie Luo; Guangying Zhang; Chen Ran; Xuling Luo (Carbon Balance and Management)
Abstract The magnitude and distribution of organic carbon (OC) transport from the terrestrial surface to the oceans is not well understood on a global scale. This hinders our understanding of terrestrial and marine carbon cycles. In this study, we determined the characteristics of OC flux. Our results showed that approximately 420 Tg C/yr of OC are transported from the terrestrial surface to the oceans, including 220 Tg C/yr of particulate organic carbon (POC) and 200 Tg C/yr of dissolved organic carbon (DOC). Asia, with only 32.46% of the basin area, accounts for 57.65% of the total POC flux, while North America, with only 17.52% of the basin area, accounts for 37.51% of DOC flux. Of these, the Pacific receives 48% of the total POC flux, and the Atlantic receives 46% of the total DOC flux. Five key zones are diagnosed and identified, in which latitudes between 5° N and 20° S contributed 72.76% of the global OC flux. Such insights directly reveal global riverine OC flux, which helps us to comprehensively understand the terrestrial and marine carbon cycles.